2010
DOI: 10.1007/s12011-010-8771-5
|View full text |Cite
|
Sign up to set email alerts
|

Multivitamin–Mineral and Vitamins (E + C) Supplementation Modulate Chronic Unpredictable Stress-Induced Oxidative Damage in Brain and Heart of Mice

Abstract: Brain is a target of stress along with the immune, metabolic, and cardiovascular systems of the body. In the present work, the preventive roles of a multivitamin-mineral supplement and vitamins (E + C) in chronic unpredictable stress (CUS)-induced oxidative damage were studied in the brain and heart of Swiss albino mice. Thirty-two mice were randomized to one of the following groups: control + vehicle, CUS + vehicle, CUS + multivitamin-mineral, and CUS + vitamins (E + C). CUS was applied for 4 weeks, and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The results showed that combined administration of MM with Ag-NPs significantly reduced serum AST and ALT levels ( P -value < 0.001). However, these results agree with Hasan et al 23 , who revealed that MM brought all stress markers' parameters to normal levels in tested mice after inducing chronic unpredictable oxidative stress. Furthermore, Namazi et al 56 have highlighted that combining an antioxidant with Ag-NPs is essential to mitigate its potential toxicity and optimize the utilization of its high efficacy.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results showed that combined administration of MM with Ag-NPs significantly reduced serum AST and ALT levels ( P -value < 0.001). However, these results agree with Hasan et al 23 , who revealed that MM brought all stress markers' parameters to normal levels in tested mice after inducing chronic unpredictable oxidative stress. Furthermore, Namazi et al 56 have highlighted that combining an antioxidant with Ag-NPs is essential to mitigate its potential toxicity and optimize the utilization of its high efficacy.…”
Section: Discussionsupporting
confidence: 92%
“…Supplementing the material proved to have synergistic action against the parasite. However, this was accepted according to Hasan et al 23 , who mentioned that MM can diminish all stress parameters, mainly oxidative stress. In addition, Namazi et al 56 noted that an antioxidant administration combined with Ag-NPs is needed to alleviate its toxicity and allow the body to benefit from its high efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic stress has been described as a risk factor for cardiovascular diseases (Lagraauw, Kuiper et al 2015), liver diseases (Russ, Kivimaki et al 2015;Kang, Zhao et al 2020) and obesity (Stefanaki, Pervanidou et al 2018). In addition, redox imbalance upon stress exposure has been described in organs such as the liver (Zaidi, Al-Qirim et al 2005;Ohta, Chiba et al 2007;Cakir, Kasimay et al 2010;Kaida, Ohta et al 2010;Kour and Bani 2011;Kalaz, Evran et al 2012;Demirdas, Naziroglu et al 2016;Kim, Oh et al 2016;Samarghandian, Farkhondeh et al 2016;Samarghandian, Azimi-Nezhad et al 2017b;Yi and Kim 2017;Lee, Jo et al 2019), the gastrointestinal tract (Cakir, Kasimay et al 2010;Banji, Banji et al 2014), the kidneys (Demirdas, Naziroglu et al 2016;Samarghandian, Farkhondeh et al 2016;Samarghandian, Azimi-Nezhad et al 2017b;Chen, Feng et al 2018), the pancreas (Lopez-Lopez, Jaime et al 2016) and the muscles (Hasan, Bilal et al 2011;Hussien, El-Wakeel et al 2019). It has been suggested that the stress-induced redox imbalance in peripheral organs is mediated by glucocorticoids (Zafir and Banu 2009b) as well as catecholamines and adrenoceptors (Zhu, Gu et al 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%